Interaksi Hiperpersonal dalam Penerapan Computer-Mediated Communication Akun Instagram @anneavantieheart - Imanuel Deny Krisna Aji; Benigna Devi Kalalo; Kuncoro Dewi Rahmawati (Calathu: Jurnal Ilmu Komunikasi, 2023)
The Instagram account @anneavantieheart has been developed by a leading designer in Indonesia, Anne Avantie. The Instagram account has been verified and has 1.1 M followers on February 2023. The development of the digital era has made many public figures use various media to interact with followers who always hope to get new information from them. The social media platform Instagram is used by Anne Avantie for establishing communication with the public, especially her followers. The Instagram account @anneavantieheart become one of the channels used in Computer-Mediated Communication (CMC). The application of interaction between Instagram account owners @anneavantieheart and their followers seen from a perspective in the application of CMC is the aim of this study. The researchers uses the descriptive qualitative research method by conducting interviews with the social media maintenance officer, owner, and followers of @anneavantieheart Instagram account. Research shows that the application of CMC is carried out by the sender of the message to make the recipient feel closer to the message. The process of hyperpersonal interaction that occurs in the application of CMC to the Instagram account @anneavantieheart fulfills four elements, namely receivers in the context of Instagram social media where followers have a positive impression of the sender of the message. However, having exaggerated expectations. Sender is done by providing categories of uploaded content, namely daily life, inspiration, spirituality, and business promotion. Channels, Instagram social media are asynchronous which allows the account manager or social media maintenance officer to plan and produce regular and quality content. Feedback can be captured directly through the comments and direct message features and indirectly through Instagram analytics. Keywords: Hyperpersonal Interaction Perspectives, Computer-Mediated Communication, Instagram, Anne Avantie